A Janovec‐Kay‐Dunn‐Like Behavior at Thickness Scaling in Ultra‐Thin Antiferroelectric ZrO2 Films. (12th September 2021) - Tasneem, Nujhat; Yousry, Yasmin Mohamed; Tian, Mengkun; Dopita, Milan; Reyes‐Lillo, Sebastian E.; Kacher, Josh; Bassiri‐Gharb, Nazanin; Khan, Asif Islam
Abstract: Originally based on phenomenological observations, the Janovec–Kay–Dunn (JKD) scaling law has been historically used to describe the dependence of the ferroelectric coercive fields ( E c ) on a critical length scale of the material, wherein the film thickness ( t ) is considered the length scale, and E c ∝ t −2/3 . Here, for the first time, a JKD‐type scaling behavior is reported in an antiferroelectric material, using the ultra‐thin films of prototypical flourite‐structure binary oxide, zirconia. In these films, a decrease in the ZrO2 layer thickness from 20 nm to 5.4 nm leads to an increase in critical fields for both nonpolar‐to‐polar ( E a ), and polar‐to‐nonpolar ( E f ) transitions, accompanied by a decrease in the average crystallite size, and an increase in the tetragonal distortion of the non‐polar P 42 / nmc ground state structure. Notably, the ‐2/3 power law as in the JKD law holds when average crystallite size ( d ), measured from glancing‐incident X‐ray diffraction, is considered as the critical length scale— i . e ., E a, E f ∝ d −2/3 . First principles calculations suggest that the increase of tetragonality in thinner films contributes to an increase of the energy barrier for the transition from the non‐polar tetragonal ground state to the field‐induced polar orthorhombic phase, and in turn, an increase in E a critical fields. These results suggest a de‐stabilization of the ferroelectric phase with a decreasing thickness in antiferroelectric ZrO2, which is contrary to the observations in its fluorite‐structure ferroelectric counterparts. With the recent interests in utilizing antiferroelectricity for advanced semiconductor applications, our fundamental exposition of the thickness dependence of functional responses therein can accelerate the development of miniaturized, antiferroelectric electronic memory elements for the complementary metal‐oxide‐semiconductor based high‐volume manufacturing platforms. Abstract : A Janovec–Kay–Dunn‐type scaling behavior is reported for the first time in antiferroelectric, fluorite‐structured zirconia (ZrO2 ) thin films. Decreasing film thickness leads to a decrease in average crystallite size, and an increase in the tetragonal distortion of the non‐polar P 42 / nmc ground state structure, ultimately resulting in an increase in critical fields for both non‐polar to polar ( E a ) and polar to non‐polar ( E f ) transitions.